PENGARUH BIMBINGAN KELOMPOK DENGAN PENDEKATAN BIBLIOTHERAPY TERHADAP MOTIVASI BELAJAR SISWA KELAS XI MA MIFTAHUL ULUM SUREN - Muhammad Yusuf Hariri; Nasruliyah Hikmatul Maghfiroh; Ika Romika Mawaddati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning motivation is a crucial aspect of the educational process. However, in practice, some students still exhibit low learning motivation, characterized by a lack of active participation, poor concentration, insufficient persistence in completing tasks, and a lack of interest in learning activities. This study aims to determine the effect of group guidance using a bibliotherapy approach on the learning motivation of Grade XI students at MA Miftahul Ulum Suren. The study employs a quantitative approach using an experimental method—specifically, a pre-experimental design known as the One-Group Pretest-Posttest Design. The population consisted of 106 Grade XI students, while the sample comprised 26 students selected via purposive sampling. Data were collected using a learning motivation questionnaire based on specific indicators: the desire to succeed, the drive and need to learn, future aspirations and goals, appreciation for learning, engaging learning activities, and a conducive learning environment. The intervention was administered through group guidance sessions incorporating a bibliotherapy approach. Data analysis was conducted using both descriptive and inferential statistics—specifically the Paired Sample t-Test—with the aid of IBM SPSS software. The results indicate that the students' average learning motivation score rose from 58.85 at the pretest stage to 83.85 at the posttest stage, representing a mean increase of 25.00 points. Hypothesis testing yielded a significance value (Sig. 2-tailed) of 0.015 (less than 0.05); consequently, the alternative hypothesis (Ha) was accepted, and the null hypothesis (H₀) was rejected. The findings demonstrate that group guidance using a bibliotherapy approach has a significant positive effect on enhancing students' learning motivation.